Thermal insulation of military boots using a thermal foot manikin in cold environments - Minhee Lee; Maria Stenkina; Yongheon Yeo; Joo-Young Lee (Fashion and Textiles)
Abstract The purpose of this study was to investigate the thermal insulation of military boots using a thermal foot manikin, and to examine environmental and technical factors to determine their thermal insulation. Three Korean and four US military boots were chosen along with four occupational boots. All measurements were conducted at air temperatures of 21, 0, and − 5 °C with an airflow of < 0.15 m s−1. The following two calculations of thermal insulation were compared: (1) a method using values obtained from all nine zones of the foot manikin [entire-zone method], and (2) a method using values from only zones covered by the boot [partial-zone method]. The results showed that the total insulation (I T) of the 11 protective boots ranged from 0.9 to 1.2 clo per boot and no differences in thermal insulation across the three air temperatures were found. Thermal insulation had a significant and strong relationship with the thickness of the boot layer (r = 0.905, P < 0.001), whereas there was no relationship between the thermal insulation and the boot mass. The thermal insulation of military boots was 81% explained by the thickness of the boot layer alone, and 94% by both the thickness of the boot layer and boot mass (P < 0.001). Thermal insulation based on the partial-zone method was 26% greater than the values using the entire zone method. We proposed design strategies for military boots according to zonal power consumption.